Anti-Inflammatory Effect of a Peptide Derived from the Synbiotics, Fermented Cudrania tricuspidata with Lactobacillus gasseri, on Inflammatory Bowel Disease - Jimyeong Ha; Hyemin Oh; Nam Su Oh; Yeongeun Seo; Joohyun Kang; Min Hee Park; Kyung Su Kim; Shin Ho Kang; Yohan Yoon (Mediators of Inflammation, 2020)
The objective of this study was to evaluate the effects of peptides derived from synbiotics on improving inflammatory bowel disease (IBD). Five-week-old male C57BL/6 mice were administered with dextran sulfate sodium (DSS) via drinking water for seven days to induce IBD (IBD group). The mice in the IBD group were orally administered with PBS (IBD-PBS-positive control), Lactobacillus gasseri 505 (IBD-Pro), fermented powder of CT extract with L. gasseri 505 (IBD-Syn), β-casein: LSQSKVLPVPQKAVPYPQRDMP (IBD-Pep 1), or αs2-casein: VYQHQKAMKPWIQPKTKVIPYVRYL (IBD-Pep 2) (both peptides are present in the synbiotics) for four more days while inducing IBD. To confirm IBD induction, the weights of the animals and the disease activity index (DAI) scores were evaluated once every two days. Following treatment of probiotics, synbiotics, or peptides for 11 days, the mice were sacrificed. The length of the small and large intestines was measured. The expression of the proinflammatory cytokines IL-1β, IL-6, TNF-α, and COX-2 in the large intestine was measured. Large intestine tissue was fixed in 10% formalin and stained with hematoxylin and eosin for histopathological analysis. The body weights decreased and DAI scores increased in the IBD group, but the DAI scores were lower in the IBD-Pep 2 group than those in the IBD group treated with PBS, Pro, Syn, or Pep 1. The lengths of the small and large intestines were shorter in the IBD group than in the group without IBD, and the expression levels of the proinflammatory cytokines were lower (p<0.05) in the IBD-Pep 2 group than those in the IBD-PBS-positive control group. In addition, histopathological analysis showed that IBD was ameliorated in the Pep 2-treated group. These results indicate that Pep 2 derived from αs2-casein was effective in alleviating IBD-associated inflammation. Thus, we showed that these peptides can alleviate inflammation in IBD.